(untitled) (World Bulletin of Social Sciences, 2022)
This article highlights the issues related to the digitalization of education at the present stage of development of society. The author points out the effectiveness of using the author’s multimedia educational program entitled “Physical culture and sport” in pedagogical universities, as well as the role of using digital technologies in physical culture lessons